CENTRAL ALDAN GOLD DEPOSITS - Vetluzhskikh V.G.; Kazansky V.I.; Kochetkov A.Ya.; Yanovsky V.M. (My University, 2002)
The Central Aldan ore district stands out in many features against the other gold districts within the Aldan Shield. The gold, uranium, and other mineral deposits are located at a junction of regional structures, they originated within a relatively short time interval of about 100 Ma, the ore mineralization is closely spatially and genetically related to alkaline magmatism, the igneous rocks and related ore deposits are located within a concentric-radial structure, and the host rocks consist of basement and sedimentary cover contrasting in physicochemical properties. All these features allow us to consider the Central Aldan district as an endogenous oremagmatic system. The Aldan complex of primarily ore-bearing alkaline basaltic crustal-mantle volcanic and plutonic rocks originated during four to five stages and numerous intrusive phases and extensive magma differentiation in mature continental crust including thin horizontally heterogeneous platform cover. Some facts considered in this paper allowed us, however, to comprise the whole series of Central Aldan gold deposits as an endogenous-exogenous ore-forming system characteristic of the tectonically activated regions of ancient platforms. The evolution of the Central Aldan district in the Jurassic, Cretaceous, and Cenozoic developed during the tectonic activation of Precembrian structures, oxidation of primary ores and weathering crust formation, and exposure of the Lebedinsk-, Kuranakh-, Ryabinovsk-, and Samolazovsk-type gold deposits to the erosion level. The formation of underground and surficial karst systems was initiated during the Jurassic weathering of carbonate rocks of the platform cover in subaerial environments. The endogenous stage of ore concentration was here directly followed by an exogenous stage with the formation of weathered rocks and gold placers in various morphostructural local environments, e.g., horsts, grabens, and graben valleys. Specific features of the placer structures and gold quality in various placer types are related with hypogene ore bodies and elements of ore-controlling structures and zones of primary disseminated mineralization. The ore bodies of the Kuranakh and Samolazovskoe deposits actually belong to new types of endogenous-exogenous deposits. The gold dispersion and concentration related to karst formation are also significant in this ore district. Thus, Central Aldan is also an ore-placer district with specific features.